2022
DOI: 10.1101/2022.05.16.22275133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial intelligence enabled retinal vasculometry for prediction of circulatory mortality, myocardial infarction and stroke

Abstract: AimsWe examine whether inclusion of Artificial Intelligence (AI)-enabled retinal vasculometry (RV) improves existing risk algorithms for incident stroke, myocardial infarction (MI) and circulatory mortality.MethodsAI-enabled retinal vessel image analysis processed images from 88,052 UK Biobank (UKB) participants (aged 40-69 years at image capture) and 7,411 EPIC-Norfolk participants (aged 48-92). Retinal arteriolar and venular width, tortuosity and area were extracted. Prediction models were developed in UKB u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…It also seems unlikely that retinal assessment alone could be used as a risk predictor, but it could indeed form part of a comprehensive CVD risk assessment incorporating other clinical risk factors. Even using AI, in this study by Rudnicka et al 21 around 20% of the images were not of sufficient quality to be assessed using QUARTZ. Looking to the future, there have been numerous studies reporting consistent associations between retinal vascular parameters and CVD prognosis.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…It also seems unlikely that retinal assessment alone could be used as a risk predictor, but it could indeed form part of a comprehensive CVD risk assessment incorporating other clinical risk factors. Even using AI, in this study by Rudnicka et al 21 around 20% of the images were not of sufficient quality to be assessed using QUARTZ. Looking to the future, there have been numerous studies reporting consistent associations between retinal vascular parameters and CVD prognosis.…”
mentioning
confidence: 65%
“…Software tools have been developed to semi-automate the analysis of the retinal vasculature, [14][15][16][17] and morphometric measures such as vessel tortuosity, diameter and fractal dimension have again been associated with increased CVD risk in multiple studies. [18][19][20] Taking this a step further, in this issue, the paper by Rudnicka et al 21 describes the use of a fully automated artificial intelligence (AI)-enabled retinal assessment tool for prediction of CVD risk in two large population cohorts. The software tool, QUARTZ, computes estimates of vessel width, area and tortuosity efficiently.…”
mentioning
confidence: 99%
“…Galtran et al [99] recently showed, through a detailed evaluation, that the performance of a simple downgraded UNet was equal to that of more complex models (several orders of magnitude in terms of model parameters) for vessel segmentation on fundus and OCT-A images. They also highlighted that these systems still exhibited a decreased performance across databases, leaving room for further improvements before application in daily clinical routine.…”
Section: Automated Image Processing With Ai Techniquesmentioning
confidence: 99%